Where do knowledge-intensive firms locate in Germany?—An explanatory framework using exponential random graph modeling - Mathias Heidinger; Fabian Wenner; Sebastian Sager; Paul Sussmann; Alain Thierstein (Review of Regional Research, 2023)
This paper analyzes how positional and relational data in 186 regions of Germany influence the location choices of knowledge-based firms. Where firms locate depends on specific local and interconnected resources, which are unevenly distributed in space. This paper presents an innovative way to study such firm location decisions through network analysis that relates exponential random graph modeling (ERGM) to the interlocking network model (INM). By combining attribute and relational data into a~comprehensive dataset, we capture both the spatial point characteristics and the relationships between locations. Our approach departs from the general description of individual location decisions in cities and puts extensive networks of knowledge-intensive firms at the center of inquiry. This method can therefore be used to investigate the individual importance of accessibility and supra-local connectivity in firm networks. We use attributional data for transport (rail, air), universities, and population, each on a~functional regional level; we use relational data for travel time (rail, road, air) and frequency of relations (rail, air) between two regions. The 186 functional regions are assigned to a~three-level grade of urbanization, while knowledge-intensive economic activities are grouped into four knowledge bases. This research is vital to understand further the network structure under which firms choose locations. The results indicate that spatial features, such as the population of or universities in a~region, seem to be favorable but also reveal distinct differences, i.e., the proximity to transport infrastructure and different valuations for accessibility for each knowledge base. – – In diesem Beitrag wird analysiert, wie Positions- und relationale Daten in 186~Regionen Deutschlands die Standortentscheidungen wissensbasierter Unternehmen beeinflussen. Es wird ein innovativer Weg zur Untersuchung solcher Standortentscheidungen von Unternehmen durch Netzwerkanalyse vorgestellt, der exponential random graph modeling (ERGM) mit dem Interlocking Network Model (INM) verbindet. Durch die Kombination von Attribut- und relationalen Daten in einem umfassenden Datensatz erfassen wir sowohl die räumlichen Punkteigenschaften als auch die Beziehungen zwischen den Standorten. Unser Ansatz weicht von der allgemeinen Beschreibung individueller Standortentscheidungen in Städten ab und stellt umfangreiche Netzwerke von wissensintensiven Unternehmen in den Mittelpunkt der Untersuchung. Mit dieser Methode kann daher die individuelle Bedeutung von Erreichbarkeit und überörtlicher Konnektivität in Firmennetzwerken untersucht werden. Wir verwenden attributive Daten für Verkehr (Bahn, Flugzeug), Universitäten und Bevölkerung, jeweils auf funktionaler regionaler Ebene; wir verwenden relationale Daten für Reisezeit (Bahn, Straße, Flugzeug) und Häufigkeit von Beziehungen (Bahn, Flugzeug) zwischen zwei Regionen. Die 186 funktionalen Regionen werden einem dreistufigen Urbanisierungsgrad zugeordnet, während die wissensintensiven Wirtschaftstätigkeiten in vier Wissensbasen gruppiert werden. Die Ergebnisse zeigen, dass räumliche Merkmale wie die Bevölkerungszahl oder die Anzahl der Universitäten in einer Region günstig zu sein scheinen, aber auch deutliche Unterschiede aufweisen, z. B. die Nähe zur Verkehrsinfrastruktur und die unterschiedliche Bewertung der Erreichbarkeit für jede Wissensbasis.
Keywords: 910; Locational choice; Firm networks; Transport infrastructure; Knowledge economy